The effect of digital literacy and transformational leadership on employee performance mediated by innovative work behavior at the Padang city population and civil registration service - Isnandar Putra; Laura Syahrul; Yulihasri (Institute of Computer Science (IOCS), 2023)
This study aims to see the effect of digital literacy and transformational leadership on employee performance with innovative work behavior as a mediating variable. Research conducted on Department of Population and Civil Registration of the City of Padang. The population in this study were all employees of the state civil apparatus (ASN) and non-state civil servants (Non ASN) of the Padang City Population and Civil Registration Service. The sample collection technique is a saturated sample, that is the entire population is used as a sample 74 people. The data analysis technique uses Structural Equation Modeling (SEM) using Smart PLS 4. The results of the study show that digital literacy and transformational leadership have no effect on employee performance. Digital literacy and transformational leadership variables affect innovative work behavior and innovative work behavior affects employee performance. Indirectly digital literacy affects employee performance through mediation of innovative work behavior and transformational leadership influences employee performance through innovative work behavior as mediation.